Analysis of Tuberculosis Control (Case Study in The City of Mojokerto) Year 2024 - Yahya, Mokhamad Suyono; Setiaji, Bambang (Syntax Corporation, 2024)
This study aims to analyze the tuberculosis (TB) situation in Mojokerto City, focusing on the increase in cases among children and identifying effective countermeasures. TB, a preventable and curable infectious disease caused by Mycobacterium tuberculosis, is particularly problematic in developing countries like Indonesia due to high incidence and mortality rates, necessitating a comprehensive control strategy. Employing qualitative methods, this research delves into the practices, perceptions, and social dynamics affecting TB control efforts in Mojokerto, illuminated by the latest data showing a significant increase in pediatric TB cases and the public health situation. Findings reveal a TB incidence rate of 385 per 100,000 inhabitants, a case detection rate of 75%, and a notably high pediatric TB case proportion of 32%. The effectiveness of case tracking by health centers varies, with an average of only 54% receiving Tuberculosis Preventive Therapy (TPT). Major obstacles include limited access to radiology services, social stigma, and the need for adequate health facilities. Innovations such as the